Coagulantes químicos e naturais para tratamento de efluentes gerados em postos de lavagem de veículos - Oliveira, Danielle Martins Cassiano de (2014)
The increase of problems related to water scarcity lead to strengthen the alternative reuse. The treatment of effluents with the purpose of reusing it can be an effective means. This study sought to test three chemical coagulants between natural and comparing them as to their effectiveness in assay of coagulation / flocculation coagulants such as natural and Tanfloc SG, Moringa oleifera, aluminum sulfate chemical. It was used an experimental planning central composite rotational design (CCRD) to determine the optimum conditions for better removal of color, turbidity, COD, solids, total nitrogen and surfactants, as well as evaluate the pH and conductivity in the presence of coagulants. The independent variables chosen for the application of the method were concentration and time. Concentrations were tested for a range of coagulation / flocculation seeking choosing the range to be inserted into the CCRD method. Through the DCCR were specified concentrations and times used in the test for the jug concentration was within 200 to 800 mg / L to SG Tanfloc SG in the range of 100 to 400 mg / L and aluminum sulfate of 300 to 800 mg / L. The coagulant considered as a better efficiency in was the natural coagulant Tanfloc SG. It has shown the best clarification of the effluent, with 93.45% of color removal and 97.82% of turbidity removal, which provides a good recirculated effluent for washing stations and better acceptance by consumers. In addition this method didn´t have problems with conductivity and removed much of the soap present in raw wastewater.